2018
DOI: 10.1186/s13104-018-3494-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment differences between genders in a low-stakes objective structured clinical examination (OSCE)

Abstract: ObjectivePhysicians and medical students are generally poor-self assessors. Research suggests that this inaccuracy in self-assessment differs by gender among medical students whereby females underestimate their performance compared to their male counterparts. However, whether this gender difference in self-assessment is observable in low-stakes scenarios remains unclear. Our study’s objective was to determine whether self-assessment differed between male and female medical students when compared to peer-assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
8
30
0
2
Order By: Relevance
“…10 This was especially true of women. 14 It has also been shown that the more the time spent in learning and practicing a skill, the higher one's self-confidence about those skills (point C), regardless of objective improvement. For example, residents' competence across milestones increases with years of training.…”
Section: Applicability To Residency Trainingmentioning
confidence: 99%
“…10 This was especially true of women. 14 It has also been shown that the more the time spent in learning and practicing a skill, the higher one's self-confidence about those skills (point C), regardless of objective improvement. For example, residents' competence across milestones increases with years of training.…”
Section: Applicability To Residency Trainingmentioning
confidence: 99%
“…Prior objectives for medical educators based on this earlier research were to focus on issues regarding female student’s confidence and perceptions 7. More recently, Madrazo (et al) found that females underestimated their performance in clinical exams 12. More specific gender differences have been illustrated with regard to the interaction of anxiety (higher anxiety improved accuracy of self-assessment for females but not in males) 13.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research indicates the accuracy of selfassessment of clinical performance is affected by such factors as gender, task familiarity, and years in medical study [10][11][12]. On the other hand, some studies have shown medical students can act as effective peer exam-iners [8,[13][14][15][16][17] and that student-led OSCEs constitute a sustainable cost-effective approach [15].…”
Section: Introductionmentioning
confidence: 99%